CCAAT/enhancer binding protein β Induces Post-Switched B Cells to Produce Blimp1 and Differentiate into Plasma Cells - Lee, Geonhee (Immune Netw, 2020)
Long-lasting post-switched plasma cells (PCs) arise mainly from germinal center (GC) reactions, but little is known about the mechanism by which GC B cells differentiate into PCs. Based on our observation that the expression of the transcription factor CCAAT/enhancer binding protein β (C/EPBβ) is associated with the emergence of post-switched PCs, we enquired whether a cell-autonomous function of C/EPBβ is involved in the program for PC development. To address this, we generated C/EPBβ-deficient mice in which the Cebpb locus was specifically deleted in B cells after transcription of the Ig γ1 constant gene segment (Cγ1). In response to in vitro stimulation, B cells from these Cebpb(fl/fl)Cγ1(Cre/+) mice had defects in the induction of B lymphocyte-induced maturation protein 1 (Blimp1) and the formation of IgG1(+) PCs, but not in proliferation and survival. At steady state, the Cebpb(fl/fl)Cγ1(Cre/+) mice had reduced serum IgG1 titers but normal IgG2c and IgM titers. Moreover, upon immunization with T-dependent Ag, the mice produced reduced levels of Ag-specific IgG1 Ab, and were defective in the production of Ag-specific IgG1 Ab-secreting cells. These results suggest that a cell-autonomous function of C/EPBβ is crucial for differentiation of post-switched GC B cells into PCs through a Blimp1-dependent pathway.